Novel antibody against low‐n oligomers of tau protein promotes clearance of tau in cells via lysosomes. Issue 1 (28th October 2020) - Chandupatla, Ram Reddy; Flatley, Andrew; Feederle, Regina; Mandelkow, Eva‐Maria; Kaniyappan, Senthilvelrajan
Abstract: Introduction: Tau, a natively unfolded soluble protein, forms abnormal oligomers and insoluble filaments in several neurodegenerative diseases, including Alzheimer disease (AD). Tau‐induced toxicity is mainly due to oligomers rather than monomers or fibrils. Methods: We have developed monoclonal antibodies against purified low‐n tau oligomers of the tau repeat domain as a tool to neutralize tau aggregation and toxicity. In vitro aggregation inhibition was tested by thioflavin S, dynamic light scattering (DLS), and atomic force microscopy (AFM). Using a split‐luciferase complementation assay and fluorescence‐activated cell sorting (FACS), the inhibition of aggregation was analyzed in an N2a cell model of tauopathy. Results: Antibodies inhibited tau aggregation in vitro up to 90% by blocking tau at an oligomeric state. Some antibodies were able to block tau dimerization/oligomerization in cells, as measured by a split‐luciferase complementation assay. Antibodies applied extracellularly were internalized and led to sequestration of tau into lysosomes for degradation. Discussion: Novel low‐n tau oligomer specific monoclonal antibody inhibits Tau oligomerization in cells and promotes toxic tau clearance.